2004
DOI: 10.1074/jbc.m308523200
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Enhancement of β-Hexosaminidase Activity in Fibroblasts from Adult Tay-Sachs and Sandhoff Patients

Abstract: Tay-Sachs and Sandhoff diseases are lysosomal storage disorders that result from an inherited deficiency of beta-hexosaminidase A (alphabeta). Whereas the acute forms are associated with a total absence of hexosaminidase A and early death, the chronic adult forms exist with activity and protein levels of approximately 5%, and unaffected individuals have been found with only 10% of normal levels. Surprisingly, almost all disease-associated missense mutations do not affect the active site of the enzyme but, rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 37 publications
4
177
0
2
Order By: Relevance
“…Protein misfolding has been implicated in many lysosomal storage disorders, such as Gaucher disease (Alfonso et al 2005), Fabry disease (Fan et al 1999), GM1 gangliosidosis (Tropak et al 2004), and Pompe disease (Parenti et al 2007). In this paper we demonstrated that, besides the p.I1061T NPC mutant protein, other 6 NPC1 mutant variants are unstable and subjected to an increased rate of proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein misfolding has been implicated in many lysosomal storage disorders, such as Gaucher disease (Alfonso et al 2005), Fabry disease (Fan et al 1999), GM1 gangliosidosis (Tropak et al 2004), and Pompe disease (Parenti et al 2007). In this paper we demonstrated that, besides the p.I1061T NPC mutant protein, other 6 NPC1 mutant variants are unstable and subjected to an increased rate of proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…NGT, a sulfur analogue of the oxazolinium ion intermediate formed during substrate turnover, was found to be an excellent candidate with a K i of 300 nM. 11 Subsequent screens identified PYR as a potential PC having many favorable qualities such as its ability to cross the blood-brain barrier and the fact that it was already FDA approved, thereby eliminating the need for expensive preclinical trials. 13 The encouraging results from a small phase I/II clinical trial of PYR for late onset G M2 gangliosidosis have recently been reported.…”
Section: Hexb:ngt Vs Hexb:pyrmentioning
confidence: 99%
“…10 Several molecules that act as inhibitors of HexA and HexB have been identified as potential pharmacological chaperones (PC) for late-onset G M2 gangliosidosis, including known inhibitors of Hex such as N-acetylglucosamine thiazoline (NGT). 11 Additionally, two libraries have been screened, the Maybridge library 12 (50 000 compounds) and the NINDs library 13 (1040 FDA approved compounds). These screens have led to the discovery that pyrimethamine (PYR, 5-(4-chlorophenyl)-6-ethyl-2,4-pyrimidinediamine) is also a good candidate for a PC.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular β-N-acetylhexosaminidase activity-Adult Tay-Sachs (homozygous for alpha subunit G269S mutation) and infantile Sandhoff (homozygous for the 16-kb HEXB deletion mutation) fibroblasts 11 were treated with an escalating dose of 6a (dissolved in DMSO) for 5 days. Intracellular β-N-acetylhexosaminidase A/S activity was measured using the fluorogenic substrate 4-methylumbelliferyl N-acetylglucosamine-6-sulfate as previously described.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…10 More recently, hexosaminidase inhibitor 3 was examined as a pharmacological chaperone for lysosomal β-Nacetylhexosaminidase A/S (Hex A/S) in fibroblasts derived from patients with Sandhoff and Tay-Sachs diseases. 8,11 Following up on our observation that some fluorescently labelled derivatives of the Dglucosidase inhibitor 2,5-dideoxy-2,5-imino-D-mannitol (DMDP) are powerful inhibitors exceeding the parent compound's activity by two orders of magnitude, 12 we have reported the syntheses and glycosidase inhibitory activities of various pyranoid N-alkylated iminoalditols featuring fluorescent tags such as dansyl moieties attached to simple Nsubstituents. 13 Based on their encouraging inhibitory activities, we envisaged more convenient properties with compounds providing a suitably positioned amine for tagging as well as an additional 'handle' for chain extension and with a view to variation of the Nsubstituent's chemical as well as biochemical properties.…”
Section: Introductionmentioning
confidence: 99%